(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
Topic: The link of Psychiatry and the Analytical Behavioral Therapy using Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-V). Aim: explore the use of a diagnostic manual based on the behavioral theory. Thesis under analysis: behavior analytic principles recommend does not focus only on the topography of behaviors. The diagnostic and statistical manual focuses only on the topography of symptoms, using an approach not based on a specific theory. Although seemingly conflicting, it is possible to connect the concepts of behavioral theory to psychiatric nosology. Sources used: published literature and study of a clinical case of a 9 year old children diagnosed with oppositional-defiant disorder according to DSM-V. Conclusion: the use of diagnostic manuals can be a strategy for the therapist who uses the Behavior Analysis as a principle in his practice. This use can influence in the assessment, planning and treatment efficacy.